A better world : a novel [large type] - Langan, Sarah (Thorndike Press, a part of Gale, a Cengage Comany, 2024)
"You'll be safe here. That's what the greasy tour guide tells the Farmer-Bowens when they visit Plymouth Valley, a walled-off company town with clean air, pantries that never go empty, and blue-ribbon schools. On a very trial basis, the company offers to hire Linda Farmer's husband, a numbers genius, and relocate her whole family to this bucolic paradise for the .0001%. Though Linda will have to sacrifice her medical career back home, the family jumps at the opportunity. They'd be crazy not to take it. With the outside world literally falling apart, this might be the Farmer-Bowens last chance. But fitting in takes work. The pampered locals distrust outsiders, cruelly snubbing Linda, Russell, and their teen twins. And the residents fervently adhere to a group of customs and beliefs called Hollow...but what exactly is Hollow? It's Linda who brokers acceptance by volunteering her medical skills to the most powerful people in town with their pet charity, ActHollow. In the months afterward, everything seems fine. Sure, Russell starts hyperventilating through a paper bag in the middle of the night, and the kids have drifted like bridgeless islands, but living here's worth sacrificing their family's closeness, isn't it? At least they'll survive. The trouble is, the locals never say what they think. They seem scared. And Hollow's ominous culminating event, the Plymouth Valley Winter Festival, is coming. Linda's warned by her husband and her powerful new friends to stop asking questions. But the more she learns, the more frightened she becomes. Should the Farmer-Bowens be fighting to stay, or fighting to get out?"--